Winning at any cost: Identity fusion, group essence, and maximizing ingroup advantage - Buhrmester, M; Newson, M; Vazquez, A; Hattori, W; Whitehouse, H (Taylor and Francis, 2018)
From verbal abuse to physical intimidation of opponents, some ingroup members seek to maximize their group’s competitive edge regardless of personal repercussions. What motivates such extreme commitment? Based on identity fusion theory, we argue that strongly fused persons seek ingroup victory at any cost when they believe that a competition’s outcome affects the group’s essence. Two studies, conducted across four countries and in two sports contexts, revealed that fused persons who believed one’s national sport constituted part of the nation’s essence were especially likely to maximize their ingroup’s advantage over the outgroup, even when doing so came at a personal cost and harmed the outgroup. Together, our findings shed new light on the motives of fused persons in intergroup conflict.